In vitro digestibility of goat milk and kefir with a new standardised static digestion method (INFOGEST cost action) and bioactivities of the resultant peptides. Issue 7 (8th July 2015) - Nehir El, Sedef; Karakaya, Sibel; Simsek, Sebnem; Dupont, Didier; Menfaatli, Esra; Eker, Alper Tolga
<x xml:space="preserve">Abstract</x> The hydrolysis degrees of goat milk and kefir during simulated gastrointestinal digestion and some bioactivities of the resulting peptides after fermentation and digestion were studied.